PENGARUH STABILISASI ASPAL EMULSI TERHADAP KARAKTERISTIK LAPISAN TANAH DASAR YANG BERASAL DARI TANAH LUNAK - Syahril, Syahril; Suratman, Ilyas; Sugeng Subagio, Bambang; Siegfried, Siegfried (Jurnal Transportasi, 2011)
Subgrade is an important part in road pavement construction, which serves as the foundation and must have the ability to bear the traffic load applying on the surface of the pavement. This study examined changes in the carrying capacity of soft soil after stabilization process using asphalt emulsion. The results of this study indicate that the stabilization process using asphalt emulsion can lower the Plasticity Index and increase the dry density and strength of the soil.Keywords: subgrade, stabilization, asphalt emulsion, Plasticity Index, dry density, soil strength.